2012
DOI: 10.1002/lsm.22105
|View full text |Cite
|
Sign up to set email alerts
|

Transepidermal retinoic acid delivery using ablative fractional radiofrequency associated with acoustic pressure ultrasound for stretch marks treatment

Abstract: Ablative fractional RF and acoustic pressure US associated with retinoic acid 0.05% cream is safe and effective for alba-type SD treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 12 publications
4
39
0
3
Order By: Relevance
“…16 Application of topical retinols, fruit acids, vitamin C, and other medicaments have been recommended for the treatment of striae rubra in its early stages, but all have moderate efficacy. 17,18 Topical tretinoin improve the appearance of striae rubra significantly [19][20][21][22] ; however, it is contraindicated in breastfeeding or pregnant women due to its probable teratogenic side effects. 23,24 Several studies have reported the improvement of the clinical appearance of striae with 585-nm pulsed dye laser (PDL) via enhancement of the extracellular matrix collagen.…”
Section: Introductionmentioning
confidence: 99%
“…16 Application of topical retinols, fruit acids, vitamin C, and other medicaments have been recommended for the treatment of striae rubra in its early stages, but all have moderate efficacy. 17,18 Topical tretinoin improve the appearance of striae rubra significantly [19][20][21][22] ; however, it is contraindicated in breastfeeding or pregnant women due to its probable teratogenic side effects. 23,24 Several studies have reported the improvement of the clinical appearance of striae with 585-nm pulsed dye laser (PDL) via enhancement of the extracellular matrix collagen.…”
Section: Introductionmentioning
confidence: 99%
“…This device was designed to cause thermal damage and fractional ablation to the tissue, while allowing for the introduction of drugs or cosmeceuticals into the dermis [6][7][8][9][10]. This method consists of the creation of microchannels, which theoretically cross the Dermo-Epidermal Junction, and through which the introduction of topically applied substances can be forced by means of ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…These microchannels can be created using a fractional CO 2 laser [9] or radiofrequency [10]. Immediately after, ultrasound is used to permeabilize the channels and force the topically applied products through them to the interior of the dermis [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations